Potato snakin-1 gene enhances tolerance to Rhizoctonia solani and Sclerotinia sclerotiorum in transgenic lettuce plants - Darqui, Flavia Soledad; Radonic, Laura Mabel; Trotz, Paulina M.; Lopez, Nilda Ester; Vazquez Rovere, Cecilia; Hopp, Horacio Esteban; Lopez Bilbao, Marisa Gisela (Elsevier, 2019)
Snakin-1 is a cysteine-rich antimicrobial peptide (AMP) isolated from potato tubers, with broad-spectrum activity. It belongs to the Snakin/GASA family, whose members have been studied because of their diverse roles in important plant processes, including defense. To analyze if this defensive function may lead to disease tolerance in lettuce, one of the most worldwide consumed leafy vegetable, we characterized three homozygous transgenic lines overexpressing Snakin-1. They were biologically assessed by the inoculation with the fungal pathogens Rhizoctonia solani and Sclerotinia sclerotiorum both in vitro and in planta at the greenhouse. When in vitro assays were performed with R. solani on Petri dishes containing crude plant extracts it was confirmed that the expressed Snakin-1 protein has antimicrobial activity. Furthermore, transgenic lines showed a better response than wild type in in vivo challenges against R. solani both in chamber and in greenhouse. In addition, two of these lines showed significant in vivo protection against the pathogen S. sclerotiorum in challenge assays on adult plants. Our results show that Snakin-1 is an interesting candidate gene for the selection/breeding of lettuce plants with increased fungal tolerance.